Optimizing Care for Patients With Adverse Events From Immunotherapeutics. Issue 6 (November 2020) - Sheehan, Kelsey; Price, Christina; Hafez, Navid
Abstract : Abstract: Immune-related adverse events (irAEs) are a common occurrence in patients treated with immune checkpoint inhibitors. Fortunately, the majority of irAEs are mild and easily managed with steroids. As the use of immune checkpoint inhibitors and other immune therapies continues to increase across indications, so too will the need for managing irAEs. Optimal care for irAEs should include surveillance and early detection, guideline-driven management of standard irAEs, multidisciplinary expert involvement in complicated or steroid-refractory cases, and concurrent research to define predictive biomarkers and delineate the populations, which can be safely treated and retreated with immune therapies. In this article, we describe the implementation of a 3-pronged strategy used at our institution consisting of an Immune Wellness Clinic to risk stratify and monitor at-risk patients, an Immuno-Oncology Treatment Monitoring Repository to support translational research, and an Immunotoxicity Tumor Board to manage severe or complicated adverse events.